Effectiveness of MCP in Overseeing Government's Internal Supervision: A Case Study of Riau's Local Governments - Meri Putri Abadi (Aptisi Transactions On Technopreneurship (ATT), 2023)
The purpose of this study is to evaluate the implementation of the Monitoring Center for Prevention (MCP) of the Corruption Eradication Commission in the supervision area of the Government Internal Supervision Apparatus (APIP) in the Riau Province area for the 2021 period, as well as input on strategies for improvement. The method used is a qualitative descriptive case study. Data processing is carried out through document analysis and interviews with regional inspectors in the Riau Province area. This study used the George Edward III model approach as an evaluation criterion. Four factors influence the successful implementation of policies/programs, namely communication, resources, disposition (disposition or attitude), and bureaucratic structure. The results of the 2021 MCP evaluation in the Riau Province area in the APIP area have been running with a score of 71%. The MCP improvement strategy needs to emphasize APIP competence and the independence of regional inspectorates. To strengthen the role of APIP, it is necessary to prepare special regulations related to the independence of the inspectorate in the regions that are MCP indicators / sub-indicators in the APIP area. The anomaly of corruption cases with MCP monitoring at the APIP level that is already running is still one of the elements of control activities, so there are many other factors to increase the MCP APIP area in efforts to eradicate corruption.